2022
DOI: 10.1002/ehf2.13896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of catheter ablation for atrial fibrillation on atrial and ventricular functional mitral regurgitation

Abstract: Aims The purpose of this study was to compare the impact of catheter ablation on cardiac structural reverse remodelling and atrial (AFMR) and ventricular (VFMR) functional mitral regurgitation (MR), and the long‐term prognosis of patients with AFMR and VFMR. Methods and results The retrospective study included persistent AF patients who had AFMR (n = 136, left atrial (LA) volume index >30 mL/m2 and left ventricular (LV) ejection fraction ≥40%) or VFMR (n = 31, LV ejection fraction <40% or LV regional asynergy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
(39 reference statements)
1
10
1
Order By: Relevance
“…Similar findings were also reported regarding functional mitral regurgitation in AF patients [ 32 ]. These results confirm that the benefit of rhythm strategy in AF patients may surpass that of symptomatic relief and extend to the improvement in morbi-mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were also reported regarding functional mitral regurgitation in AF patients [ 32 ]. These results confirm that the benefit of rhythm strategy in AF patients may surpass that of symptomatic relief and extend to the improvement in morbi-mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have reported reductions in vena contracta and effective regurgitant orifice area as well as improvements in MR severity after conducting rhythm control in those with AFMR secondary to AF. [33][34][35] This is attributed to the restoration of sinus rhythm exhibiting atrial reverse remodeling, thereby reducing the degree of annular dilatation. 34,35 The 2020 Japanese Circulation Society heart valve disease management guideline gives an IIa recommendation to consider catheter ablation in symptomatic patients with AF and severe functional MR if maintenance of sinus rhythm can be expected, but nothing regarding this is mentioned in American and European guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported reductions in vena contracta and effective regurgitant orifice area as well as improvements in MR severity after conducting rhythm control in those with AFMR secondary to AF 33–35 . This is attributed to the restoration of sinus rhythm exhibiting atrial reverse remodeling, thereby reducing the degree of annular dilatation 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a cohort of 136 AFMR individuals who underwent atrial fibrillation ablation, MR decreased in 64%, and only in those patients the LA volume also decreased. 15 Patients who had sinus rhythm restored had less MR and more reduction in LA volume than those who did not. The extent of low-voltage areas in the LA thought to reflect left atrial fibrosis and correlated with less reduction in MR and LA volume, suggesting that in the presence of extensive low-voltage areas AFMR may not be improved by ablation even if sinus rhythm is restored.…”
Section: Treatment and Outcomesmentioning
confidence: 91%